Impact of climate adaptation strategies on the net farm revenue of underutilised indigenous vegetables’ (UIVs) production in Southwest Nigeria - Tanimonure, V.A.; Naziri, D. (Elsevier, 2021)
This paper examined the impact of climate adaptation strategies employed by Underutilised Indigenous Vegetables (UIVs) farmers on UIVs’ net revenue of adopters and non-adopters of adaptation strategy in Southwest Nigeria. This was with a view to determine the factors that determined UIVs net revenue in the study area. Both quantitative and qualitative primary household data from 191 UIVs producers, with secondary climate data from Nigeria Meteorological agency were used. An efficient endogenous switching regression model (ESRM) was used to estimate the effect of climate change adaptation strategy on UIVs net revenue. The results show that farmers’ perception of climate change showed a high temperature and a high variability in rainfall pattern. The adaptation strategies mostly employed by the UIVs farmers is cultivating along river banks (98%) while the least was agroforestry and perennial plantation (4%). Meanwhile, all the farmers who adopted farmers that adopted Agroforestry and perennial plantation and Agricultural good practices did not experience loss in UIVs production. The factors that determined the likelihood of adopting climate adaptation strategy include years of experience (0.0335, p<0.1) in UIVs production, access to climate information (0.7895, p<0.1) and agro ecological zone (0.7889, p<0.1). Further, factors that determine the net revenue from UIVs for adopters were access to information on climate change 0.2428, p<0.1), off-farm income (0.6526, p<0.01), precipitation (0.0045, p<0.1), precipitation square (0.−0.00002, p<0.1) and Ondo location (0.4470, p<0.05). Age (0.1261, p<0.1), agro ecological zone (4.2682, p<0.1), off-farm income (−1.1765, p<0.05) and precipitation square (0.0001, p<0.01) determined the UIVs revenue for non-adopters. The promotion of UIVs should therefore be advocated by the government and non-government agencies since high temperature does not have significant effect on its revenue. Also, provision of relevant information on climate change is essential for farmers as this will enhance farmers’ likelihood of adopting appropriate climate change adaptation strategy considering the type of crop they cultivate and the peculiarity of their agro ecological zones. Also, vegetables’ farmers are encouraged to engage in agroforestry and perennial plantation.